2015
DOI: 10.3168/jds.2015-9676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed selenium supplementation on milk selenium distribution and mozzarella quality

Abstract: In the present study, the effect of feed Se supplementation on the Se content of raw milk and mozzarella cheese as well as the effect on cheese quality and functionality were determined. The Se milk was produced by supplying dairy cow feed with Se yeast (0.3mg of Se/kg of dry matter), resulting in a Se concentration in milk of 35.81μg/L. The fat, casein, and whey protein of Se milk were separated by ultracentrifugation, and the Se content was determined by atomic absorption spectroscopy. The Se distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…However, salt addition in high concentrations would decrease the proteolytic activity of the enzymes, increasing water loss from the protein network, resulting in lower moisture and, in turn, an increase in firmness of the cheese (Zhang et al, 2014). This agrees with Liu et al (2015), who have indicated that the higher the moisture content in cheese, the lower the firmness.…”
Section: Composition Of Mozzarella Cheese Stickssupporting
confidence: 92%
See 2 more Smart Citations
“…However, salt addition in high concentrations would decrease the proteolytic activity of the enzymes, increasing water loss from the protein network, resulting in lower moisture and, in turn, an increase in firmness of the cheese (Zhang et al, 2014). This agrees with Liu et al (2015), who have indicated that the higher the moisture content in cheese, the lower the firmness.…”
Section: Composition Of Mozzarella Cheese Stickssupporting
confidence: 92%
“…Most whey was drained, and pH reached 5.3-5.6 (Jana and Mandal, 2011). After that, it was kneaded in hot water (0.33 L water L -1 milk) at 80-85°C for 2-3 min (Jana and Mandal, 2011;Liu et al, 2015), obtaining the elastic texture of mozzarella cheese. The mozzarella sticks were formed when the curd reached 54-66°C (Liu et al, 2015;Moynihan et al, 2016).…”
Section: Mozzarella Sticks Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mehdi and Dufrasne (2016) indicated that cows supplemented orally with organic selenium showed an increase in milk selenium concentrations of 190% higher than those that received inorganic selenium. Liu et al (2015) found elevated selenium concentrations in cheese manufactured from milk of supplemented cows.…”
Section: Introductionmentioning
confidence: 99%
“…Diante disso, e tendo em vista que a composição de selênio nos laticínios é diretamente influenciada pelo consumo da ração, uma alternativa interessante seria suplementar a ração animal com selênio a fim de garantir uma concentração mais elevada nos produtos resultantes da atividade leiteira Liu, Zhu, Lu, Wei, Ren (2015); Ling et al (2017).…”
Section: Resultsunclassified